Immunomodulatory Hydrogels: Advanced Regenerative Tools for Diabetic Foot Ulcer. (1st January 2023) - Xiong, Yuan; Feng, Qian; Lu, Li; Zha, Kangkang; Yu, Tao; Lin, Ze; Hu, Yiqiang; Panayi, Adriana C.; Nosrati‐Ziahmagi, Vahideh; Chu, Xiangyu; Chen, Lang; Shahbazi, Mohammad‐Ali; et al.
Abstract: Diabetic foot ulcer (DFU) is one of the most common complications of diabetes, bringing physical and mental challenges for patients due to the lack of efficient curative therapy. Despite considerable advances in pharmacological and surgical approaches, clinical trials for DFU patients remain disappointing due to the local overactive and excessive inflammation. Immunomodulatory hydrogels has significant advantages to overcome the clinical challenge of DFUs therapy. Here, recent fabrication and regenerative advances in the utilization of functional hydrogels for altering the immune microenvironment of DFUs are comprehensively reviewed. The pathological features and the healing processes of DFUs, followed by summarizing the physicochemical properties essential for the design of regenerative hydrogels for immunomodulation in DFUs, are briefly introduced. Then, the potential immuno‐therapeutic modalities of hydrogels and emerging trends used to treat DFUs via multitherapeutic approaches and enhanced efficacy and safety are discussed. Taken together, by linking the structural properties of hydrogels to their functions in DFU therapy with a particular focus on immunomodulatory stimuli, this review can promote further advances in designing advanced hydrogels for DFUs, resulting in improved diabetic wound repair through translation into clinical setting in the near future. Abstract : Herein, advances are discussed in the utilization of hydrogels to promote the therapy of diabetic foot ulcer by altering the immune microenvironment. By addressing the importance of the structural property of hydrogels and current challenges in the design of multifunctional immunomodulatory systems to manipulate biological responses, this review promotes the knowledge required to translate hydrogels into clinical setting in the future.